Book Reviews. Issue 2 (1st June 2022) - Unknown
Abstract : Barbara Bassot (2020), The Research Journal: A Reflective Tool for Your First Independent Research Project . Bristol: Policy Press, 188 pp., ISBN: 978-1-4473-5278-5 David J. Staley (2019), Alternative Universities: Speculative Design for Innovation in Higher Education . Baltimore: Johns Hopkins University Press, 268pp., ISBN: 978-1-4214-2741-6 Keyan G. Tomaselli (2021), Contemporary Campus Life: Transformation, Manic Managerialism and Academentia . Cape Town: Best Red, 245pp., ISBN: 978-1-928246-26-8